Heavy Metal Levels in Post-Coal Mining Lakes Used for Tilapia (Oreochromis niloticus) Farming with Floating Net Cage System in South Kalimantan - Kusnadi, Iwan Sugiarto; Nurhasanah, Nurhasanah (Biotropika: Journal of Tropical Biology, 2025)
This study evaluated tilapia (Oreochromis niloticus) cultivation using the Floating Net Cage (FNC) system in a post-mining lake of PT Arutmin Indonesia, South Kalimantan. The main objective of this study was to measure the content of heavy metals arsenic (As), cadmium (Cd), and lead (Pb) in water and fish organs to ensure consumption safety. Data collection was conducted in April–June 2022, and the analysis results showed that the highest levels of As and Cd were accumulated in the liver and gills of fish, but were still below the safe threshold. Meanwhile, lead was not detected in all samples. Based on the t-test, no significant differences were found between organs in metal content. These results indicate that the waters and fish from the lake are safe for human consumption. This study supports the use of post-mining land for productive and sustainable activities that are economically beneficial to the surrounding community.